OPTIMIZING BSI MOBILE BANKING SERVICE THROUGH A THREE-DIMENSIONAL ANALYSIS : SOCIAL MEDIA, EXTERNAL AND INTERNAL - Wahyudi, Wahyudi; Wandebori, Harimukti (LPPM STIE Muhammadiah Bandung, 2025)
The rise of mobile banking in Indonesia underscores the strategic role of platforms like BSI Mobile in meeting customer expectations. This study examines user perceptions of BSI Mobile services using big data from X (formerly Twitter) as a real-time source of public opinion. Sentiment data from X was analyzed using the CRISP-DM framework, employing the Naive Bayes method for category and sentiment classification, which was then mapped onto the Importance-Performance Matrix (IPM). External analysis, using PESTEL, Porter's Five Forces, and competitor analysis, highlighting general, industry and competitor challenges. Internally, resource evaluations conducted through value chain analysis and the VRIO framework revealed that transitioning from BSI Mobile to the BYOND platform is a strategic step to strengthen technical and operational capabilities. The findings indicate an urgent need to enhance the app’s features and functionalities, followed by improvements in speed, reliability, security, and UI/UX. The study underscores the importance of strengthening both offline and online marketing strategies to promote BYOND’s features and functionalities, leveraging its Unique Selling Proposition (USP) as a sustained competitive advantage to drive digital adoption among both existing and new customers. Big data analytics helps identify improvements and track service performance.